2002
DOI: 10.1007/s10265-002-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of carbon balance for reproduction in woody species

Abstract: The carbon balance in reproductive organs over the whole reproductive period was estimated for 20 woody species on the basis of the published data on the final dry weight and CO(2) exchange of reproductive organs. The relationship between net respiration and dry weight growth was formulated by a linear function with a negative y-intercept. From this linear relationship, linear relations of dry weight growth and net respiration to net translocation were derived. The size dependence of net respiration showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Therefore, woody plants are divided into three groups, in which CO 2 release by dark respiration is less than, equal to, or greater than CO 2 refixation by photosynthesis, depending on the size of the reproductive organ. According to the analysis, the net respiration changed from positive to negative at final dry mass (w) ϭ 0.481 g as w decreased (Ogawa, 2002). The average fruit dry mass for E. japonica at the final stage was 0.072 g, much smaller than the estimated threshold (w ϭ 0.481 g), and developing fruits of E. japonica are green.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, woody plants are divided into three groups, in which CO 2 release by dark respiration is less than, equal to, or greater than CO 2 refixation by photosynthesis, depending on the size of the reproductive organ. According to the analysis, the net respiration changed from positive to negative at final dry mass (w) ϭ 0.481 g as w decreased (Ogawa, 2002). The average fruit dry mass for E. japonica at the final stage was 0.072 g, much smaller than the estimated threshold (w ϭ 0.481 g), and developing fruits of E. japonica are green.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, photosynthesis in fruits may contribute to their carbon requirements, thereby potentially reducing the relative cost of fruit production. Ogawa (2002) estimated the carbon balance in reproductive organs for 20 woody species over the entire reproductive period. He showed that the relationship between net respiration and dry-mass growth was formulated by a linear function with a negative y-intercept.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies of CO 2 exchange have concentrated on detached fruit (Ogawa 2002), but to our knowledge, there are no reports describing the temporal patterns of CO 2 exchange over the whole reproductive process. Moreover, very few studies have examined CO 2 exchange in the reproductive organs of tropical woody species (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Using the compartment model for estimating carbon balance in a reproductive organ (Ogawa 2002(Ogawa , 2004, daily net translocation into an organ (DTr, mg dw organ -1 day -1 ) (Hozumi and Kurachi 1991) was calculated as follows:…”
Section: Estimation Of Carbon Balance In Fruits and Leavesmentioning
confidence: 99%